Impact of Gonadotropin-releasing Hormone Analogue and Gender-affirming Hormone Therapy on Bone Mineral Density in Transgender Adolescents - Marta Chuncia; Witold Czyż; Julia Kacperczyk; Filip Arczewski; Karol Dziedzic; Julia Kulbacka; Maciej Wojszczyk; Damian Zys; Piotr Pasek; Julia Ryniecka (Quality in Sport)
Background: Sex hormones have a key impact on the development of the human body during puberty, including a significant influence on bone development - their shape, structure, length, and mineral density. Due to the growing number of transgender and gender diverse (TGD) adolescents and the increasing demand for gender-affirming hormone therapy (GAHT), there is rising curiosity about the impact of this therapy on the developing body of a young person.